Biceps Box Configuration for Superior Capsule Reconstruction of the Glenohumeral Joint Decreases Superior Translation but Not to Native Levels in a Biomechanical Study - Patrick J. Denard, M.D; Seungbum Chae, M.D; Christen Chalmers, B.S; Jae Hyuk Choi, B.S.E; Michelle H. McGarry, M.S; Gregory Adamson, M.D; Max Park, M.D; Thay Q. Lee, Ph.D (Elsevier, 2021)
Purpose: To quantitatively biomechanically assess superior stability, subacromial contact pressures, and glenohumeral kinematics of an in situ biceps tenodesis and a box-shaped long head of the biceps tendon (LHBT) superior capsule reconstruction (SCR) in a superior massive rotator cuff tear (MCT) model. Methods: Eight cadaveric shoulders (mean age, 62 years; range, 46-70 years) were tested with a custom testing system used to evaluate range of motion, superior translation, and subacromial contact pressure at 0°, 20°, and 40° of abduction. Conditions tested included native state, MCT (complete supraspinatus and one-half of the infraspinatus), a box-shaped LHBT SCR, and an in situ biceps tenodesis. The box-shaped SCR was performed by maintaining the biceps origin, securing 2 corners to the greater tuberosity, and one corner to the posterior glenoid. The in situ tenodesis was performed anatomically at the top of the articular margin in the same shoulder after take-down of the box SCR. Results: Range of motion was not impaired with either repair construct (P > .05). The box SCR decreased superior translation by approximately 2 mm compared with the MCT at 0°, but translation remained greater compared with the intact state in nearly every testing position. The in situ tenodesis had no effect on superior translation. Peak subacromial contact pressure was increased in the MCT at 0° and 20° abduction compared with the native state but not different between the native and box SCR at the same positions. Conclusions: A box-shaped SCR using the native biceps tendon partially restores increased superior translation and peak subacromial contact pressure due to MCT. The technique may have a role in augmentation of an irreparable MCT. Clinical Relevance: The box-shaped LHBT SCR technique may have a role in augmentation of an irreparable MCT.